1962
DOI: 10.1149/1.2425276
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Iron-Nickel Alloys

Abstract: The oxidation of Fe-Ni alloys in the 500~176 range has been the subject of many investigations. These observations are summarized, and an attempt is made to generalize on the kinetics and mechanism of oxidation. The composition of the oxide film over the entire composition range can be explained in terms of the thermodynamic stability of the oxides of Fe, of NiO, and of Ni,Fe~_zO,. In alloys of all compositions that have been investigated the first reaction is one of selective oxidation, creating a Ni-rich met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1967
1967
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…Based on the mechanism, we have proposed that Fe 2 O 3 formation promotes a-Al 2 O 3 formation; thus, this critical Fe concentration must also be linked to initial Fe 2 O 3 formation. Foley et al studied oxidation of the binary Ni-Fe alloy system and reported that Fe 2 O 3 was formed on Ni-70 and 59Fe alloys but not on Ni-22Fe alloy at temperatures from 600 to 900°C in air [22]. Although only several data points are available from their study, the critical Fe content to form Fe 2 O 3 obtained in this study broadly agrees with their findings.…”
Section: Suppression Of Metastable Al 2 O 3 Formationsupporting
confidence: 86%
“…Based on the mechanism, we have proposed that Fe 2 O 3 formation promotes a-Al 2 O 3 formation; thus, this critical Fe concentration must also be linked to initial Fe 2 O 3 formation. Foley et al studied oxidation of the binary Ni-Fe alloy system and reported that Fe 2 O 3 was formed on Ni-70 and 59Fe alloys but not on Ni-22Fe alloy at temperatures from 600 to 900°C in air [22]. Although only several data points are available from their study, the critical Fe content to form Fe 2 O 3 obtained in this study broadly agrees with their findings.…”
Section: Suppression Of Metastable Al 2 O 3 Formationsupporting
confidence: 86%
“…If the interface composition had reached point d in Figure 2, the oxidation rate would be controlled by iron diffusion in the c-iron phase, rather than iron ion migration in the oxide. For binary ironnickel alloys, oxidation rates decrease by two to three orders of magnitude compared to pure iron, [26] when diffusion in the solid metal controls the overall oxidation rate. This is significantly larger than the decrease measured here.…”
Section: Discussionmentioning
confidence: 99%
“…Foley reported that the rate constant (K p ) of the Fe-29.6%Ni alloy oxidized at 1000 o C for 0~60 min in an air atmosphere is 3.3×10 -9 g 2 /cm 4 · sec [9]. When compared with the rate constants of the Fe-29.6%Ni alloy with those of the Fe-30%Ni-12.5%Co alloy, the rate constant of the Fe-30%Ni-12.5%Co alloy was higher than that of the Fe-29.6%Ni alloy.…”
Section: Kinetics Of High Temperature Oxidationmentioning
confidence: 99%
“…As a result, a complex oxide of the Fe 3-x Ni x O 4 (0<x 1) type is formed besides Fe 2 O 3 and Fe 3 O 4 , and NiO sometimes appears at the high Ni content region near the interface [7]. However, it has been reported that the results of studies on Fe 3-x [9]. Meanwhile, in the study of the oxidation of the Fe-Ni Invar alloy [4,7,10] it has been performed under the atmosphere of CO/CO 2 , vacuum and air under 1100 o C. The effect of additive elements such as Mn, Cr, Si, Ca, S and P over 1000 o C have been investigated from a standpoint of oxidation and its kinetics of the Fe-Ni based alloy [11].…”
Section: Introductionmentioning
confidence: 99%